Penerapan Metode Klasifikasi Perangkat Lunak ArcMap pada Pemetaan Penyebaran Penyakit Dengue di Bandung - Ananda Shafira; Farah Kristian; Benny Yong (Limits: Journal of Mathematics and Its Applications, 2023)
Bandung is the city with the highest cases of Dengue disease in West Java. The effectiveness of the vaccine of Dengue disease are still not very high and there is no specific medicine for Dengue disease. In this study, we estimate the relative risk of Dengue disease in each sub-district in Bandung. The results of the relative risk estimation can be used as a reference to cure and prevent this disease more effective and efficient because we can focus more on critical area. The relative risks are estimated using two approaches, the frequentist with the Standardized Morbidity Ratio (SMR) model and Bayesian with the Localized model of Bayesian Conditional Autoregressive (CARBayes). The results show that the sub-districts with the highest and lowest relative risk are Cibeunying Kidul and Bandung Kulon, respectively. Furthermore, each sub-districts are depicted based on their relative risk using some classification methods. The classification methods from ArcMap software that will be used are Manual Interval, Defined Interval, Equal Interval, Quantile, Natural Breaks, and Standard Deviation. The classification results with each method show that each method has its own characteristics.